Immigrants and gender roles: Assimilation vs. culture - Francine Blau (IZA Journal of Migration, 2015)
This paper examines evidence on the role of assimilation versus source country culture in influencing immigrant women's behavior in the United States-looking both over time with immigrants' residence in the United States and across immigrant generations. It focuses particularly on labor supply but, for the second generation, also examines fertility and education. We find considerable evidence that immigrant source country gender roles influence immigrant and second generation women's behavior in the United States. This conclusion is robust to various efforts to rule out the effect of other unobservables and to distinguish the effect of culture from that of social capital. These results support a growing literature that suggests that culture matters for economic behavior. At the same time, the results suggest considerable evidence of assimilation of immigrants. Immigrant women narrow the labor supply gap with native-born women with time in the United States, and, while our results suggest an important role for intergenerational transmission, they also indicate considerable convergence of immigrants to native levels of schooling, fertility, and labor supply across generations.
Keywords: J13; J16; J22; J24; J61; 330; Gender; Immigration; Labor supply; Wages; Social capital; Culture; Human capital; Migranten; Frauen; Kultur; Soziale Integration; Arbeitsangebot; Fertilität; Frauenbildung; USA